2005
DOI: 10.1152/ajpgi.00542.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol feeding and folate deficiency activate hepatic endoplasmic reticulum stress pathway in micropigs

Abstract: Previously, we showed that feeding micropigs ethanol with a folate-deficient diet promoted the development of hepatic injury while increasing hepatic levels of homocysteine and S-adenosylhomocysteine (SAH) and reducing the level of S-adenosylmethionine (SAM) and the SAM-to-SAH ratio. Our present goals were to evaluate mechanisms for hepatic injury using liver specimens from the same micropigs. The effects of ethanol feeding or folate-deficient diets, singly or in combination, on cytochrome P-450 2E1 (CYP2E1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
95
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 45 publications
12
95
1
Order By: Relevance
“…30 Ethanol-induced hyperhomocysteinemia has been proposed to play a role in alcoholic liver injury. 31,32 As shown in Fig. 2D, PUFA ϩ E feeding increased plasma homocysteine by approximately 1.4-fold over PUFA alone, and the HSF ϩ E diet increased homocysteine approximately 2.9-fold as compared with the HSF-fed control animals.…”
Section: A Hsf Diet Attenuated Hepatic Steatosis and Reversed Alaninementioning
confidence: 76%
“…30 Ethanol-induced hyperhomocysteinemia has been proposed to play a role in alcoholic liver injury. 31,32 As shown in Fig. 2D, PUFA ϩ E feeding increased plasma homocysteine by approximately 1.4-fold over PUFA alone, and the HSF ϩ E diet increased homocysteine approximately 2.9-fold as compared with the HSF-fed control animals.…”
Section: A Hsf Diet Attenuated Hepatic Steatosis and Reversed Alaninementioning
confidence: 76%
“…Our prior study showed that folate deficiency had additive effects that were independent of ethanol feeding on markers of liver injury (Esfandiari et al, 2005;Halsted et al, 2002). Therefore, to promote abnormal methionine metabolism while enhancing ER stress and liver injury, all micropigs were placed on folate depleted diets and were divided into 3 different groups (n 5 6) that included: (1) control, (2) ethanol, and (3) ethanol plus SAM at 0.4 g/ 1,000 kcal.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…One hundred milligrams of each liver tissue sample was homogenized, nuclear extracts were prepared, and Western blots were performed as described previously (Esfandiari et al, 2005). Western blot analyses were carried out using multispecies antibodies to SREBP-1c (Santa Cruz Biotechnologies, Santa Cruz, CA), antiAMPKa and b, anti-phospho-AMPKa and b (Cell Signaling Technology, Beverly, MA), and anti-b-actin (1:10,000) (Sigma, St. Louis, MO).…”
Section: Tissue Fractionations and Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations